Asuhan Kebidanan Ibu Hamil Trimester III dengan Nyeri Punggung Belakang - Sarnilam Cahya; Lili Purnama Sari (Jurnal Pembaruan Kesehatan Indonesia, 2025)
Lower back pain is a common complaint experienced by some pregnant women, especially in the third trimester due to physiological changes in pregnancy such as weight gain, changes in the body's center of gravity, and softening of the ligaments. This pain can reduce the quality of life and daily activities of pregnant women. This study aims to explore and describe midwifery care provided to pregnant women in the third trimester with complaints of lower back pain through a case study approach. This study uses a qualitative method with a case study design. The subject of the study was a pregnant woman in the third trimester who came with complaints of lower back pain. Data collection was carried out through in-depth interviews, observations, and documentation studies. The midwifery care provided includes interventions in the form of providing midwifery care through non-pharmacological therapy, namely warm compresses on the lower back area (lumbar) for 15-20 minutes, identification of risk factors, provision of health education, ergonomic body position exercises, relaxation techniques. The results of the study showed that interventions given consistently for three consecutive days can reduce the intensity of back pain, increase comfort, and improve the posture of pregnant women. Clients also showed increased knowledge about how to manage pain independently. The conclusion of this study is that integrated midwifery care that focuses on the individual needs of pregnant women has proven effective in reducing complaints of lower back pain. This case study can be a reference for health workers in providing comprehensive and holistic antenatal care.